Community Project: Boll-Arts Mural - Mohamad Faizuan, bin Mat (Borneo Posst Online, 2018)
Community Project: Boll-Arts Mural is a community project that take place on 31 March & 1 April 2018 at Waterfront, Kuching Sarawak.